SUPERVISORY FACTORS AND COUNSELLOR-IN-TRAINING COMPETENCIES IN THE SUPERVISION PROCESS - Suhaili Arifin; Siti Salina Abdullah; Masturina Ahamad; Nordiana Abd Rahim; Nor Akmariah Abdullah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Supervision process is a mandatory component in counsellor education and training to produce competent counsellor-in-training. Referring to the Board of Counsellors Malaysia, counsellors’ competency is emphasised as a crucial ethic that needs to be complied with, to preserve the clients’ wellbeing. In the meantime, in every supervision relationship between the supervisor and the counsellor-in-training, there is no mistaking the fact that there are factors that can influence the increasing or decreasing level of competency among the counsellors-in-training. That said, studies about these variables in the supervision process are still scarce, particularly in the local contexts. Thus, this paper aims to propose the significant factors in the supervision process, then to develop the hypotheses of how far these factors can be linked with the competency of the counsellors-in-training. This paper also seeks to propose a conceptual framework based on the hypotheses formulated. The study respondents are the counsellors-in-training from public universities undergoing an internship training in the settings that offer counselling service nationwide. The study finding is expected to offer some contributions to some improvements in the counsellors’ education and training system in Malaysia, in years to come.